2004
DOI: 10.1128/jvi.78.15.7938-7944.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Infectious Pancreatic Necrosis Virus Replication by Atlantic Salmon Mx1 Protein

Abstract: Mx proteins form a family of interferon (IFN)-induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(126 citation statements)
references
References 42 publications
3
117
1
2
Order By: Relevance
“…The genes relevant to type I IFN signaling have also been reported, such as melanoma differentiation-associated gene 5 (Mda5), toll-like receptors (TLRs), IFN receptors, IFN regulatory factor (IRF) and several downstream signaling members and ISGs (Robertsen, 2006), demonstrating that teleost fish possess an IFN antiviral system. In support of this notion, Mx (Caipang et al, 2003;Larsen et al, 2004) and PKR (Zhu et al, 2008) have been approved to exert antiviral function in fish.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The genes relevant to type I IFN signaling have also been reported, such as melanoma differentiation-associated gene 5 (Mda5), toll-like receptors (TLRs), IFN receptors, IFN regulatory factor (IRF) and several downstream signaling members and ISGs (Robertsen, 2006), demonstrating that teleost fish possess an IFN antiviral system. In support of this notion, Mx (Caipang et al, 2003;Larsen et al, 2004) and PKR (Zhu et al, 2008) have been approved to exert antiviral function in fish.…”
Section: Introductionmentioning
confidence: 91%
“…After CAB cells were treated with UV-inactivated GCHV for different time points, real-time PCR was employed to detect the expression status of Mx1, a known antiviral gene both in mammals and fish (Caipang et al, 2003;Larsen et al, 2004;. As shown in Fig.…”
Section: In Vitro Induction Of Gig2 By Uv-inactivated Gchv and Poly I:cmentioning
confidence: 99%
“…Recently virusinduced IFN genes have been characterized in various fish species (Aggad et al, 2009;Altmann et al, 2003;Long et al, 2004;Lutfalla et al, 2003;Robertsen et al, 2003;Zou et al, 2007), and some downstream ISG counterparts have also been identified (Robertsen, 2006;Zhang et al, 2007), strongly indicating that teleost fish possess an IFN antiviral system. In support of this notion, IFN inducible genes including Mx and PKR have been proved to block virus replication in fish (Caipang et al, 2003;Larsen et al, 2004;Zhu et al, 2008), and there exists a conserved RLR (RIG-I-like receptors) pathway responsible for fish IFN induction during virus infection (Biacchesi et al, 2009). Fish virus-induced IFNs exhibit more homology to mammalian type I IFN molecules on the basis of protein sequence identity, but they are not clearly an ␣-or ␤-IFN (Robertsen, 2006;Robertsen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Two types of fish IFN genes have been identified in fish genomes, one most similar to mammalian type I IFNs and the other orthologous to mammalian type II IFN (Altmann et al, 2003;Hamming et al, 2011;Stolte et al, 2008;Zou et al, 2005). These fish IFNs can establish host antiviral state by inducing the expression of many fish IFN-stimulated genes (ISGs), such as PKR, Mx, ISG15 and some novel ISGs including PKZ, Gig1 and Gig2 (Langevin et al, 2013;Larsen et al, 2004;Li et al, 2012;Liu et al, 2011;Sun et al, 2014;Zhu et al, 2008). Fish viperin homologue is firstly identified in rainbow trout Oncorhynchus mykiss (Boudinot et al, 1999), and then in other fish species (Dang et al, 2010;Lee et al, 2013;Levraud et al, 2007;Padhi, 2013;Rise et al, 2008;Sun and Nie, 2004;Workenhe et al, 2009;Zhang et al, 2014;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%